1997
DOI: 10.3109/00365529709025087
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Measurement after Rectal Excision for Cancer: Comparison between Straight and Colonic J-Pouch Anastomosis

Abstract: The Nottingham Health Profile was effective in showing an improvement in quality of life in both groups after surgery. The observed difference in clinical bowel function was not, however, reflected in an improved quality of life score as measured by the Profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 15 publications
0
27
0
2
Order By: Relevance
“…Though some aspects, such as sexual enjoyment and perception of body image proved to be worse [37], postoperative quality of life even seems to exceed preoperative values [39][40][41][42]. Additionally, postoperative quality of life after surgery for rectal cancer appears to be at least similar to that of the average population of the same age [16,43].…”
Section: Quality Of Life After Rectal Cancer Surgerymentioning
confidence: 80%
See 1 more Smart Citation
“…Though some aspects, such as sexual enjoyment and perception of body image proved to be worse [37], postoperative quality of life even seems to exceed preoperative values [39][40][41][42]. Additionally, postoperative quality of life after surgery for rectal cancer appears to be at least similar to that of the average population of the same age [16,43].…”
Section: Quality Of Life After Rectal Cancer Surgerymentioning
confidence: 80%
“…While Hallbook and co-workers [41] and Furst and colleagues [66] could not detect a difference between patients with a pouch-anal anastomosis and those with a straight anastomosis, a randomized, prospectively conducted investigation recently published by Sailer et al [40] found a significantly better quality of life in the pouch group; at least during the first postoperative year.…”
Section: Quality Of Life After Rectal Cancer Surgerymentioning
confidence: 95%
“…Only three studies were dedicated to a comprehensive assessment of QoL using well-estab-lished questionnaires with proven psychometric properties. [12][13][14] The remaining studies were found to be limited to isolated symptoms, such as sexual dysfunction and defecation-related or urologic symptoms. Most of the studies used unvalidated questionnaires.…”
Section: Resultsmentioning
confidence: 99%
“…Außerdem ist eine bessere Lebensqualität der Patienten mit ultratiefen Resektionen durch prospektive Studien nicht ausreichend belegt. Insgesamt finden sich zum Thema Lebensqualität überhaupt nur 4 Studien mit verhältnismäßig geringen Fallzahlen, die gut evaluierte Fragebö-gen mit psychometrischen Testverfahren nutzten [31,35,88,89]. Neueste Untersuchungen zeigen sogar, dass die Patienten nach LAR eine schlechtere Lebensqualität haben können als die Patienten, die einer APR unterzogen wurden [31].…”
Section: Diskussionunclassified